Cooling as social practice: heat mitigation and the making of communal space in Jakarta's informal settlements - Salsabila, Safira (2023)
The rise of Urban Heat Island (UHI) is harming people across megacities in the world. In Jakarta, the informal settlements are most affected due to the lack of adequate infrastructure to deal with the heat. The heat problem in the informal settlements was primarily exacerbated by overcrowding and a lack of access to cooling infrastructures. In this paper, we observe how residents of the informal settlements take on a cooling practice collectively. Our study is situated in five urban kampongs located in the most populated sub-districts (kelurahan) in Jakarta. Nine months of ethnographic fieldwork were conducted to unpack the residents' endeavor to mitigate the heat problem. To explicate the process and the role of these cooling facilities, we use the notion of social practice comprising three fundamental elements: competence, material, and meaning. “Social practice” aptly characterizes how the residents in each kampong worked together to build cooling places that also function as communal spaces. Our research discovered that despite limited resources and technical competence, each kampong recognized the necessity of communal spaces to maintain their cooling practices. These measures enabled them to engage in cooling practices while building social relationships through chilling outdoors. By demonstrating the capacity of residents in the informal settlements for constructing vernacular forms of cooling infrastructure, this paper offers a pluralistic view of heat mitigation in megacities of the Global South.